Impacts of Brexit on fruit and vegetable intake and cardiovascular disease in England: a modelling study - Seferidi,P; Laverty,A; Pearson-Stuttard,J; Bandosz,P; Collins,B; Guzman-Castillo,M; Capewell,S; O'Flaherty,M; Millett,C (BMJ Open, 2019)
Objectives To estimate the potential impacts of different Brexit trade policy scenarios on the price and intake of fruits and vegetables (F&V) and consequent cardiovascular disease (CVD) deaths in England between 2021 and 2030.Design Economic and epidemiological modelling study with probabilistic sensitivity analysis.Setting The model combined publicly available data on F&V trade, published estimates of UK-specific price elasticities, national survey data on F&V intake, estimates on the relationship between F&V intake and CVD from published meta-analyses and CVD mortality projections for 2021–2030.Participants English adults aged 25 years and older.Interventions We modelled four potential post-Brexit trade scenarios: (1) free trading agreement with the EU and maintaining half of non-EU free trade partners; (2) free trading agreement with the EU but no trade deal with any non-EU countries; (3) no-deal Brexit; and (4) liberalised trade regime that eliminates all import tariffs.Outcome measures Cumulative coronary heart disease and stroke deaths attributed to the different Brexit scenarios modelled between 2021 and 2030.Results Under all Brexit scenarios modelled, prices of F&V would increase, especially for those highly dependent on imports. This would decrease intake of F&V between 2.5% (95% uncertainty interval: 1.9% to 3.1%) and 11.4% (9.5% to 14.2%) under the different scenarios. Our model suggests that a no-deal Brexit scenario would be the most harmful, generating approximately 12 400 (6690 to 23 390) extra CVD deaths between 2021 and 2030, whereas establishing a free trading agreement with the EU would have a lower impact on mortality, contributing approximately 5740 (2860 to 11 910) extra CVD deaths.Conclusions Trade policy under all modelled Brexit scenarios could increase price and decrease intake of F&V, generating substantial additional CVD mortality in England. The UK government should consider the population healt